How to Solve the Social Norm Conflict Dilemma of Green Consumption: The Moderating Effect of Self-Affirmation - Ge, Wanda; Sheng, Guanghua; Zhang, Hongli (Frontiers in Psychology, 2020)
Social norms are important social factors that affect individual behavioral change. Using social norms to promote green consumption is receiving increasing attention. However, due to the different formation processes and mechanisms of the behavioral influence of the different types of social norms, using social norms to promote green consumption often has social norm conflict situations (injunctive norms + negative descriptive norms). Thus, it is difficult to attain the maximum utility of social norms. The present research found that social norm conflict weakens the role of injunctive norms in promoting green consumption. Specifically, negative descriptive norms weaken the role of injunctive norms in promoting green consumption. Alienation, which manifests through powerlessness and meaninglessness, plays a mediating role in the relationship between social norm conflict and green consumption. Self-affirmation moderates the mediating role of alienation between social norm conflicts and green consumption. Self-affirmation reduces the alienation caused by social norm conflict, thereby alleviating the weakening effect of social norm conflict on green consumption.